Optimizing resistance training for pain management in knee and hip osteoarthritis: a pairwise and dose–response meta-analysis - Liu, Wenyu; Yin, Meng; Li, Huimin (Frontiers in Public Health, 2025)
BackgroundOsteoarthritis (OA) is a degenerative joint disease affecting approximately 300 million people worldwide. OA manifests as significant pain and stiffness as well as reduced mobility, substantially impacting patient quality of life and imposing considerable financial burdens on healthcare systems. Although resistance training (RT) demonstrates therapeutic potential, existing studies vary widely in its intensity, duration, and effectiveness, necessitating comprehensive dose–response analyses.ObjectiveThis study aimed to evaluate the effectiveness of RT interventions in the management of OA pain.MethodsA systematic literature search was performed of the PubMed/MEDLINE, Embase, Cochrane Library, and Web of Science databases. Effect sizes were computed using Hedges’g, while the risk of bias was assessed using the Cochrane Risk of Bias 2 tool. Potential moderating factors including age, sex, and body mass index (BMI) were also analyzed.ResultsThe analysis included 28 randomized controlled trials (2,164 participants) that satisfied the inclusion criteria. RT significantly reduced OA pain compared to no intervention (Hedges’g = −0.57; 95% CrI, −0.65 to −0.49). A U-shaped dose–response relationship was observed, with an optimal weekly RT dose of 680 METs/min/week for pain relief. Higher or lower doses were less effective, and pain improvement was maintained for up to 6 months post-intervention. Age and sex were potential moderators, with more significant benefits observed in females and less favorable outcomes in older patients. BMI had no significant effect on RT efficacy.ConclusionRT constitutes an effective non-pharmacological intervention for reducing OA pain, at an optimal training dose of 680 METs/min/week. These findings emphasize the importance of considering individual patient characteristics, particularly age and sex, when prescribing RT for OA pain management.Systematic review registrationPROSPERO, Identifier: CRD42024622698; https://www.crd.york.ac.uk/PROSPERO/view/CRD42024622698.